Performance, emissions, and combustion characteristics of methane-diesel dual-fuel engines: A review - Tripathi, Gaurav; Dhar, Atul (Frontiers in Thermal Engineering, 2022)
Methane is highly demanded alternative fuel for internal combustion engines due to its availability in many forms such as methane hydrates, natural gas, biogas, compressed natural gas, liquid natural gas, synthetic natural gas and pipe natural gas etc. Methane can be effectively used in existing diesel engines with few modifications in dual fuel mode. Dual fuel technology is helpful in making a bridge between the existing conventional fuelled engines and alternative gaseous fuel powered conventional engines. Properties of methane such as higher calorific value, abundance diffusion and wider flammability limit make it suitable fuel for improving the performance of compression ignition engine in dual fuel mode. Methane-diesel dual fuel engine is an effective engine technology for reducing the vehicular pollution and partially replacing conventional fuels for transport applications. Therefore, a comprehensive review study is needed to document the various pathways for utilization of methane in dual fuel engines. This study critically compares the combustion, noise, performance, and emission characteristics of various methane fueled engines to bring out the current challenges and future perspective for synergistic use of methane for reducing the emissions from internal combustion engines.